A Case of Atypical Croup - Geoff Cuvelier; Amged El-Hawrani; Hamdy El-Hakim; Joan L Robinson (Canadian Journal of Infectious Diseases and Medical Microbiology)
Case Presentation A previously healthy eight-month-old girl was admitted to the pediatric intensive care unit at Stollery Children's Hospital (Edmonton, Alberta) following a waxing and waning course of respiratory distress. She had initially presented 11 days earlier to the emergency room with stridor and a brassy cough, and laryngotracheobronchitis was diagnosed. Treatment with racemic adrenaline and one dose of oral dexamethasone was effective and she was discharged after overnight observation. Nasopharyngeal aspirate was negative by direct fluorescent antibody and by viral culture for influenza A and B, parainfluenza and respiratory syncytial virus. Over the next three days, the child had increasing stridor and was admitted and again treated with racemic adrenaline and a four-day course of oral dexamethasone. She was subsequently discharged. White lesions were noted on the tongue and were treated with topical nystatin. Four days later, the child presented to the emergency room with recurrence of stridor and fever and new onset of drooling. She had a respiratory rate of 44 breaths/min, heart rate of 170 beats/min, blood pressure of 90/58 mmHg, oxygen saturation of 98% and temperature of 39.6°C. She was in moderate respiratory distress, with marked stridor. Examination of the oropharynx revealed ulcerative lesions on the anterior tongue, hard and soft palate, and posterior pharynx. Laboratory studies revealed a white blood cell count of 18.1x109/L (74% neutrophils, 23% lymphocytes and 3% monocytes). Other hematological values were normal. A laryngobronchoscopy was performed and revealed that the mucosa of the laryngopharynx was studded with discrete white lesions on a background of mucosal inflammation with severe reduction of airway calibre requiring intubation (Figure 1). The subglottis and the tracheobronchial tree were severely inflamed but had no discrete lesions.